Facilitating Mobility or Fueling Complexity? A Segment-Based Assessment of the Thailand–China Visa Waiver Agreement - Xin, Zhang (Journal of Dhamma for Life, 2025)
This study investigates the segmented impacts of the Thailand–China Mutual Visa Exemption policy implemented in March 2024. While the agreement has facilitated cross-border travel and revitalized Thailand’s inbound tourism, it has also introduced legal ambiguity, administrative strain, and symbolic friction especially among long-stay or purpose-driven travelers such as students, retirees, and job seekers. Using a mixed-methods approach, this research combines 830 survey responses with 15 in-depth interviews across five traveler groups. Findings reveal a shift in travel motivations from traditional push–pull factors to policy-enabled flexibility. While tourists benefit from ease of entry, other groups face regulatory uncertainties around visa extension, residency classification, and social legitimacy. These tensions are exacerbated by infrastructural constraints and inconsistent institutional communication. The study contributes to mobility governance theory by proposing a modified Push Pull framework incorporating trust, segmentation, and post-access frictions. Policy implications suggest the need for differentiated onboarding, traveler profiling, and real-time monitoring systems. A segment-sensitive governance model is recommended to ensure that simplification does not lead to systemic vulnerability. This research offers empirical and theoretical insights into the unintended complexities of visa liberalization and provides a roadmap for countries aiming to align accessibility with long-term sustainability.